HUBUNGAN JENIS MAKANAN DAN MINUMAN IRITATIF DENGAN SINDROMA DISPEPSIA PADA SISWA DAN SISWI SMA I ADABIAH PADANG TAHUN AJARAN 2020/2021 - Tia Reza; Dewi Mutiara (Nusantara Hasana Journal, 2025)
Dyspepsia syndrome is a collection of symptoms or syndromes consisting of pain or discomfort in the epigastrium, nausea, vomiting, bloating, early satiety, full stomach, recurrent or chronic belching. The scope of this research discipline is internal medicine. This study uses primary data by distributing questionnaires. The target population is SMA 1 Adabiah Padang students for the 2020/2021 academic year. Samples were selected by means of probability, namely simple random sampling with ordinal-ordinal correlative analytical techniques as many as 74 samples. The type of research used is analytic with a cross sectional approach. The research was conducted from September 2021 to July 2021 at SMA 1 Adabiah Padang. Data analysis using chi square test. The highest gender was female, namely 47 people (63.5%) out of 74 samples, the most frequent type of spicy food was 38 people (51.4%), the most acidic type of food was frequent, namely 40 people (54.1% ) and the most frequent type of irritating drink was 38 people (51.4%), the most positive dyspepsia syndrome was 59 people (79.7%) and there was no relationship between the type of spicy food and dyspepsia syndrome in SMA 1 Adabiah Padang (p = 0.064), there was no relationship between types of acidic foods and dyspepsia syndrome at SMA 1 Adabiah Padang (p = 0.351) and there was no relationship between types of irritating drinks and dyspepsia syndrome at SMA 1 Adabiah Padang (p = 0.064). There is no relationship between the type of spicy food and dyspepsia syndrome in SMA 1 Adabiah Padang, there is no relationship between the type of acidic food and there is no relationship between irritating drinks and dyspepsia syndrome at SMA 1 Adabiah Padang.